Fatty Acid Composition, Cholesterol and Nutritional Indices of Srinidhi and Vanaraja Chicken Varieties at 16, 20 and 24 Weeks of Age - Katekhaye, Anita; Kumar, M. Shashi; Reddy, K. Kondal; Rao , Kessava (Journal of Meat Science, 2018)
The fatty acid profile and cholesterol content were studied in Srinidhi and Vanaraja chicken varieties – slaughtered at the 16, 20 and 24 weeks. All fatty acids studied were significantly (P<0.01) influenced by age and sex. Study recorded significantly (p<0.01) less saturated fatty acid in Srinidhi and Vanaraja chicken at 24 weeks of age followed by 20 weeks and 16 weeks of age. Unsaturated fatty acid recorded significantly (p<0.01) highest in Srinidhi and Vanaraja chicken at 24 weeks of age followed by 20 weeks of age and then 16 weeks of age. MUFA decreased significantly (p<0.01) with age from 16 week to 24 weeks. This corresponded to the significant decrease in C16:1 and C18:1 in the older chickens and might be lower desaturase activity. Significantly (p<0.01)higher PUFA recorded in Srinidhi chicken than Vanaraja chicken at 24 weeks of age than Srinidhi chicken and these might be due to higher Elongase and Thioesterase indices in these birds.Study recorded positive effect of age on atherogenic and thrombogenic index, while h/H and p/s ratio increased significantly. Additionally, n-6/n-3 ratio decreased substantially in the older chickens. Cholesterol content significantly (p<0.01) less in Srinidhi chicken than Vanaraja chicken in all age group and older chicken exhibited significantly (p<0.01) higher cholesterol content as age advanced. Effect of sex dimorphism on cholesterol content also recorded significant. These results opens new prospective for further research on the breeding practices of Srinidhi and Vanaraja varieties in order to produce slow-growing chickens with beneficial fatty acid composition of meat for the consumers.